2019
DOI: 10.38038/vocatech.v1i0.11
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Inkubator Bisnis dalam Menumbuhkan Jiwa Kewirausahaan Mahasiswa Akademi Komunitas Negeri Putra Sang Fajar Blitar

Abstract: Abstrak—Inkubator Bisnis Teknologi (IBT) merupakan program untuk menumbuhkembangkan kewirausahaan yang berbasis teknologi berupa pendanaan, pelatihan, dan asistensi bagi inkubator dan tenant (pengusaha pemula) yang dilaksanakan melalui sistem kompetisi/seleksi. Sebagaimana perguruan tinggi lain di Indonesia yang menyelenggarakan mata kuliah kewirausahaan, tantangan yang dihadapi Akademi Komunitas Negeri Putra Sang Fajar Blitar (AKB) adalah menyediakan sebuah fasilitas yang dapat membantu melahirkan wirausahawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…The results also found that business incubator activity has changed the mindset of some students. Similar research carried out by Ardiansyah et al (2019) shows that business incubator activities include training and coaching as well as the formation of business units. Students cannot be separated from obstacles originating from internal and external factors.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The results also found that business incubator activity has changed the mindset of some students. Similar research carried out by Ardiansyah et al (2019) shows that business incubator activities include training and coaching as well as the formation of business units. Students cannot be separated from obstacles originating from internal and external factors.…”
Section: Introductionsupporting
confidence: 56%
“…The business incubator is a useful place to grow the entrepreneurial spirit that is creative, innovative, resilient and professional so that it can develop business (Hayati & Wijayanti, 2019). Activities undertaken by the business incubator in fostering an entrepreneurial spirit are training and coaching as well as the formation of business units at the university (Ardiansyah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing this phenomenon, there is a need to boost entrepreneurial interest among students. Various factors influence students' entrepreneurial interest, often stemming from the motivation to create something new, contribute to society, or achieve greater financial gains than being employed as a regular worker (Ardiansyah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu kegiatan BRIDA adalah menyiapkan wadah inkubator bisnis, yaitu berdasar Peraturan Gubernur Nusa Tenggara Barat Nomor 19 tahun 2022 tentang Penyelenggaraan Kawasan Inkubasi Bisnis dimana pemerintah perlu memfasilitasi tumbuh dan berkembangnya industri berbasis inovasi dan teknologi melalui penyediaan Kawasan Inkubasi Bisnis di Provinsi Nusa Tenggara Barat. Berdasar hasil riset sebelumnya, inkubasi bisnis umumnya diinisiasi oleh kampus (Ardiansyah et al, 2019;Hasbullah et al, 2014;Lutfiani et al, 2020;Siregar et al, 2019). Namun provinsi Nusa Tenggara Barat mencoba menggunakan BRIDA untuk melakukan inkubasi bisnis startup.…”
unclassified